A review of sensor applications towards precise control of pyrolysis of solid waste and biomasses. (November 2022) - Zhang, Haifeng; Ju, Shuai; Jin, Xin; Yuan, Yan; Wu, Yingji; Nadda, Ashok Kumar; Pugazhendhi, Arivalagan; Cai, Liping; Xia, Changlei
Abstract: Pyrolysis is one of the most efficient and sustainable technologies for converting biomass, solid waste into valuable bioenergy products to achieve future-oriented synthetic energy. As the intelligent automation control has been rapidly developing recently, it is desired to control and adjust the operating parameters in each feedstock reaction stage by accurately measuring the temperatures, pressures, and the produced gas quantity and compositions. This study reviews comprehensively pressure and gas sensors that are applied or potentially applied in pyrolysis. It was found that the operating temperature and reactor pressure are critical parameters affecting the yields and quality of pyrolysis products. Gas sensors can be used to detect various gases and vapors, such as methane, hydrogen, carbon monoxide, and dioxide, to estimate the quality, quantity, and compositions of gas products for their further utilizations during the pyrolysis and upgrading. According to the sensing data of the gas products, operating parameters of the pyrolysis and upgrading processes can be adjusted and optimized to enhance the pyrolysis efficiency and quality of synthetic energy products. As for the performances of available gas sensors, many of them can withstand temperatures up to 1000 °C and have advantages of good selectivity and stable for long-time, which can be utilized for pyrolysis and upgrading processes. The authors' group will develop high temperature wireless SAW gas sensor for monitoring the major gases in the reactor during pyrolysis and upgrading processes and enhance the efficiency of syn-gas production and gas quality via sensing. Graphical abstract: Image 1 Highlights: Sensors can help control operating parameters to enhance pyrolysis efficiency. Review of pressure and gas sensors that are applied/potentially applied in pyrolysis. Gas sensors can detect compositions of various pyrolysis gases and vapors. Pyrolysis operating parameters can be optimized based on the obtained sensing data. Many available gas sensors can be utilized for pyrolysis and/or upgrading processes.